Molecular biological factors in the diagnosis of cervical intraepithelial neoplasias - Yu. N. Ponomareva; I. B. Manukhin; L. A. Ashrafyan (ABV-press, 2014)
The authors have made a complex analysis of the molecular biological factors associated with cervical intraepithelial neoplasia. They have revealed that infection by oncogenic human papillomavirus types is associated with suppressed apoptosis and enhanced cellular proliferative activity, which can be effectively used in the diagnosis and prediction of cervical neoplasias to optimize management tac- tics and to improve the results of treatment.